Ozone Therapy in Papillomavirus Infection- HPV (Ozone Therapy Global Journal, 2017)
We analyze a study of 30 patients infected with human papillomavirus (HPV) without having spontaneous remission after one year as of the first diagnosis. The samples were collected between October 2014 and February 2017. Cervical swabs were analyzed both HPV genotyping by PCR and Reverse Line Blot, and cervical cytology by Pap testing. The study was carried out with the objective of verify the efficacy of O2 / O3 alone and in combination with other complementary measures. The patients were divided into two groups. a) Group O3 + (treated with ozone plus integrative therapy): It was treated with intravaginal ozone, ozonated saline solution, micro-immunotherapy and administration IV of GSH, Se, Zinc and VitC.• b) Ozone Group (treated exclusively with ozone): It was administered with intravaginal ozone therapy alone. Although the number of patients does not allow a safe conclusion, the group of patients treated with ozone plus integrative therapy presented a great advantages (p˂0,05) compared to the group of patients treated exclusively with ozone. Positive (negative cytology after 3 months of finishing the therapy) • Group O3 + (patients treated with ozone plus integrative therapy):16 de 20 => 80.0 % • Ozone group (patients treated exclusively with ozone): 6 de 10 => 60.0 % It was shown that the synergy of the ozone therapy with the other treatments was more effective, permanent and harmless than the application of intravaginal ozone alone.